Trust and transparency: Accreditation and impact reporting by Canadian charities - Christopher Nicholas Dougherty (Canadian Journal of Nonprofit and Social Economy Research, 2019)
This article examines the public reporting of impact, defined as progress towards a charity’s mission and long-term objectives, by Canadian charities through their annual reports. The public reporting behaviour of those accredited under Imagine Canada’s Standards Program is compared with a matched sample of charities that have not sought accreditation. The objective is to explore whether trust-building activities like public disclosures of impact and third-party accreditation are convergent. The study finds that accreditation status correlates with impact measurement and reporting; both trends are linked to organizational size, and accreditation does not appear to be causing charities to increase their disclosures of impact, which suggests that there may be underlying factors driving both behaviours. These findings generally affirm earlier research that correlates organizational size with impact measurement, adding that the effect is weak.